Factors Affecting Users’ Acceptance of E-Billing System in Surakarta Tax Office - Rino Ardhian Nugroho; Arlyn Dewi Susilowati; Okki Chandra Ambarwati; Arum Pratiwi (Bina Nusantara University, 2018)
This research aimed to analyze factors that affected the acceptance of e-billing system of Surakarta tax office with Unified Theory of Acceptance and Use of Technology (UTAUT) model. The survey was done on electronic billing (e-billing) system users in Surakarta. Partial Least Square-Structural Equation Modelling (PLSSEM) was used to analyze the users’ intention in adopting e-billing system. The result indicates that two UTAUT variables (performance expectancy and social influence) affect the system usage significantly. Meanwhile, the other variables like effort expectancy and facilitating conditions do not affect e-billing system adoption in Indonesia.